Multi-Criteria Teacher Performance Evaluation Using the SMART Decision Support Method - Achmad Sehan; Rezy Azril Fadillah (bit-Tech, 2026)
Teacher performance evaluation plays a strategic role in sustaining instructional quality, yet existing appraisal systems in educational settings are often designed for conventional schools and lack structured computational frameworks capable of capturing the multidimensional demands of nature-based and spiritually integrated institutions. This study develops a web-based Decision Support System (DSS) integrating the Simple Multi-Attribute Rating Technique (SMART) to operationalize teacher performance assessment at Sekolah Alam Tahfidzpreneur, which combines academic instruction, Quran memorization, entrepreneurship, and outdoor learning. Unlike prior SMART-based implementations that primarily focus on score automation, this study formalizes weight rationalization, explicit benefit–cost criteria structuring, and utility normalization to enhance decision transparency and methodological replicability. Ten performance criteria were defined and weighted through institutional policy alignment, and teacher ratings were transformed into normalized utility scores to generate composite rankings. The system produced consistent performance stratification across eleven teacher alternatives, with top-ranked scores exceeding the institutional evaluation threshold. Efficiency gains and reduced subjectivity were inferred through comparative process mapping against the prior manual interview-based approach, demonstrating shorter evaluation cycles and explicit audit trails of weighting and scoring logic. By externalizing evaluation assumptions and computational procedures, the proposed DSS strengthens accountability and supports evidence-based professional development planning. The findings demonstrate that structured multi-criteria modeling can provide a transparent and replicable governance mechanism for complex hybrid educational environments.